Adaptive Immune Resistance to Intravesical BCG in Non–Muscle Invasive Bladder Cancer: Implications for Prospective BCG-Unresponsive Trials - Max Kates; Andrés Matoso; Woonyoung Choi; Alexander S. Baras; Marcus J. Daniels; Kara A. Lombardo; Aaron Brant; Nina Mikkilineni; David J. McConkey; Ashish M. Kamat; Robert S. Svatek; Sima P. Porten; et al. (2019)
To characterize immune cell expression among patients with non-muscle invasive bladder cancer (NMIBC) treated with Bacillus Calmette-Guerin (BCG).Patients with NMIBC treated with intravesical BCG (2008-2015) were identified, and a tissue microarray was constructed using paired pre- and post-BCG bladder samples. Among patients undergoing BCG, cystoscopic evaluation began 3 months after initiating BCG treatment to determine therapeutic response. IHC was performed for CD8, CD4, FoxP3, PD-L1 (SP-142 and 22C3), and PD-1. A full slide review of PD-L1+ staining tumors was performed to characterize PD-L1 and CD8 colocalization. RNA-seq was performed on cored tumors from available specimens. We compared immune cell populations between BCG responders and nonresponders, and between pretreatment and postreatment tumor samples. Baseline PD-L1 staining in the BCG naïve population was then validated in a separate cohort.The final cohort contained 63 pretreatment NMIBC cases, including 31 BCG responders and 32 BCG nonresponders. No differences in CD4, CD8, or FoxP3 expression were identified between responders and nonresponders. Baseline PD-L1 expression (22C3 and SP-142) was observed in 25% to 28% of nonresponders and 0% to 4% of responders (P < 0.01). PD-L1+ cells in BCG nonresponders colocalized with CD8+ T cells. In addition, BCG therapy did not increase PD-L1 gene expression (RNA-seq) or protein levels (IHC). The number of pretreatment CD4+ T cells was very low among PD-L1+ nonresponders (12%) and high among PD-L1- nonresponders (50%, P < 0.01). In a separate cohort of 57 patients with NMIBC undergoing BCG, baseline PD-L1 (22C3) staining was similar (26%).One mechanism of BCG failure may be adaptive immune resistance. Baseline tumor PD-L1 expression predicts an unfavorable response to BCG and if validated, could be used to guide therapeutic decisions.